2021
DOI: 10.1038/s41598-021-90249-9
|View full text |Cite|
|
Sign up to set email alerts
|

Femtosecond laser induced low propagation loss waveguides in a lead-germanate glass for efficient lasing in near to mid-IR

Abstract: To support the growing landscape of near to mid-IR laser applications we demonstrate a range of low propagation loss femtosecond laser (FSL) written waveguides (WGs) that have achieved guided-mode laser operation in a rare earth (RE) doped lead-germanate glass. The WGs are fabricated in both the athermal and thermal FSL writing regimes using three different pulse repetition frequencies (PRF): 100 kHz (athermal); 1 MHz; and 5 MHz (thermal). The lasing capability of Yb3+ doped lead-germanate waveguides is verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The near infrared lasing attributes of as made GPGN glass are demonstrated earlier by the authors in Refs. [ 55 , 56 , 96 ]. The cumulative impact of these results reflects GPGN glass as a high potential laser gain medium for ∼ 2.1 μm applications by realizing the continuous wave single frequency laser action in a short cavity (5 mm) Ho 3+ doped GPGN glass.…”
Section: Discussionmentioning
confidence: 99%
“…The near infrared lasing attributes of as made GPGN glass are demonstrated earlier by the authors in Refs. [ 55 , 56 , 96 ]. The cumulative impact of these results reflects GPGN glass as a high potential laser gain medium for ∼ 2.1 μm applications by realizing the continuous wave single frequency laser action in a short cavity (5 mm) Ho 3+ doped GPGN glass.…”
Section: Discussionmentioning
confidence: 99%
“…It would be of practical importance for applications including, but not limited to, home automation, smartphones and even automotive applications. The few studies of infrared glasses mainly dealt with the fabrication of waveguides [13,21,22] and did not address the fabrication of free space optics or microoptics for imaging applications. In order to reach these longer wavelengths in the IR range, nonsilicate glasses such as chalcogenide [23], fluoride [24] or heavy oxide [25] glasses must be used.…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al demonstrated the fabrication of 3D Type I waveguides in barium borate glass codoping with Dy 3+ and Eu 3+ ions for the visible band applications [31]. In 2021, M. Khalid et al showed the femtosecond laser written Type II waveguides in Yb doped glass for 1 μm laser applications [32]. Compared with Type I and II, depressed cladding waveguides commonly are considered to possess better performance in fiber-to-waveguide coupling with adjustable diameter of the end-face cross-section [15,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%